Effects of zinc injection on stress corrosion cracking of cold worked austenitic stainless steel in high-temperature water environments. (November 2017) - Zhang, Lefu; Chen, Kai; Wang, Jiamei; Guo, Xianglong; Du, Donghai; Andresen, Peter L.
Abstract: In the nuclear power industry, few data exist to demonstrate the effectiveness of Zn injection in reducing the crack growth rate of primary component materials. This work shows that Zn injection reduced the stress corrosion cracks growth rate of cold worked 316L stainless steel (SS) by 3 times. ZnCr2 O4 oxide was detected both on the crack walls and at the crack tip, showing that Zn substitution in the spinel-type oxide occurred and mitigated stress corrosion cracking. Graphical abstract: